Rethinking solidarity towards equity in global health: African views - Atuire, C.A.; Hassoun, N. (International Journal for Equity in Health, 2023)
When the COVID-19 pandemic first took the world by storm, the World Health Organization (WHO) issued a Solidarity Call to Action to realize equitable global access to COVID-19 health technologies through pooling of knowledge, intellectual property and data. At the dawn of 2022, 70% of rich countries’ populations were vaccinated but only 4.6% of poor countries (Our World In Data, Coronavirus (COVID-19) vaccinations, 2022). Vaccine nationalism and rampant self-interest grew and our ineffective global response led to new variants of concern - like Omicron - emerging. Rather than abandon the idea of solidarity in global health, we believe that the international community must embrace it. Solidarity, with its emphasis on relationality and recognition of similarities, could offer fertile ground for building an ethical framework for an interconnected and interdependent world. Such a framework would be better than a framework that focuses principally on individual entitlements. To defend this view, we draw on African relational views of personhood and morality. When humans are conceived of as essentially relational beings, solidarity occupies a central role in moral behaviour. We argue that part of the reason appeals to solidarity have failed may be traced to an inadequate conceptualization of solidarity. For as long as solidarity remains a beautiful notion, practiced voluntarily by generous and kindhearted persons, in a transient manner to respond to specific challenges, it will never be able to offer an adequate framework for addressing inequities in global health in a systematic and permanent way. Drawing on this understanding of solidarity, we propose pathways to respond creatively to the risks we face to ensure equitable access to essential health for all.
Research Article
Keywords: Solidarity; Global health; African philosophy